Potential of Combination Marsilea crenata and Curcuma xanthorriza to Improve Sperm Quality of Male Mice Exposed by Monosodium Glutamate - Firstiantono, Andista; Rahayu, Sri; Warih Marhendra, Agung Pramana; Soewondo, Aris (Biotropika: Journal of Tropical Biology, 2022)
This study aims to determine the potential of water clover (M. crenata), curcuma (C. xanthorriza), and the combination of both extracts in order to improve the sperm quality of mice after MSG administration. This study used 35 Balb/C male mice (3 months old, 25-30 grams body weight (BW)). The animals randomly divided into 7 treatment groups, namely K0 (the group given MSG 4 mg/gBW), K1 (the group given MSG 4 mg/gBW and M. crenata 0.09 mg/gBW), K3 (the group given MSG 4 mg/gBW and C. xanthorriza 0.2 mg/gBW), K4 (the group that was given MSG 4 mg/gBW and a combination of M. crenata extract 0.045 mg/gBW and C. xanthorriza 0.1 mg/gBW), K5 (the group given M. crenata 0.09 mg/gBW), and K6 (the group given C. xanthorriza 0.2 mg/gBW). MSG and all extracts are given orally and daily for 30 days. The observed parameters were spermâ€™s motility, viability, and concentration. The data are analyzed using SPSS for windows with a One-way ANOVA test (pâ‰¤0.05) and Tukey HSD test. The administration of water clover, curcuma, and the combination of both extracts can significantly improve the sperm quality in mice exposed by MSG. The administration of single and combination extract can improve the motility, viability, and concentration of the sperm in treatment groups with the extract. In conclusion, the combination of water clover and curcuma ethanol extract significantly improved sperm quality.